Presentation of female nursing professionals who worked during the COVID-19 Pandemic, in 2021, and their perceptions about Nursing - Terra, Maria Fernanda; Silva, Nathalia de Oliveira (O Mundo da Saúde, 2023)
Brazilian nursing is marked by the social division of its professionals (nurses, technicians and assistants), 85% of whom are female, therefore gender stands out in the profile of the working body and in the political demands of the category, especially under the scenario of a public health crisis, such as the Covid-19 Pandemic. Thus, this research aims to present the female nursing professionals who worked in care in the 2nd year of the Covid-19 pandemic in Brazil, and their perceptions about the profession. It is a qualitative study carried out through questionnaires answered virtually by 100 women. The sample is made up of a majority of white nurses, married or in a stable union, aged between 20 and 40 years old, with children, from the southeast region, working in public institutions and with a single employment contract. When comparing the 1st and 2nd year of the pandemic, 41% declare a worsening due to the relaxation of protective measures by the population and professionals. 36% declare improvement associated with the effective organization of care. For the question “What is nursing for you?”, there were recurring statements that described a commitment that goes beyond professional status. The pandemic brought to the civil debate the importance of health care in facing this new disease that has deepened the social abysses existing in the country. This scenario may have provoked the need to adopt a more sentimentalist view to describe the profession as a strategy for emotional resilience in the face of suffering.